Successful Management of Immune Thrombocytopenia Presenting with Lethal Alveolar Hemorrhage - Keiki Nagaharu; Masahiro Masuya; Keiki Kawakami; Naoyuki Katayama (Case Reports in Hematology)
Immune thrombocytopenic purpura (ITP) typically presents with bleeding due to immunologic thrombocytopenia. Severe hemorrhage due to ITP is sometimes lethal, and the urgent recovery of platelets is necessary. In addition to conventional therapeutic strategies, romiplostim shows promising efficacy for chronic ITP. However, there is little evidence for the utilization of this treatment for acute ITP or acute exacerbation of chronic ITP. We report the case details of three elderly ITP patients presenting with lethal diffuse alveolar hemorrhage. These patients had the following underlying pulmonary diseases: case 1, nontuberculous mycobacterial infection and sarcoidosis; case 2, cryptogenic organizing pneumonia; case 3, pulmonary emphysema. These patients recovered following treatment with romiplostim at a higher dose (10 μg/kg), in addition to conventional therapies including corticosteroids and high-dose intravenous immunoglobulin. In summary, the addition of romiplostim resulted in earlier recovery of thrombocytopenia than has been previously reported. Our three cases suggest that early romiplostim at a higher dose could be an efficacious therapeutic option for acute ITP patients with severe lethal bleeding.